PRODUCTION NEED GAPS OF HOUSEHOLDS IN PEPPER PRODUCTION FOR ALLEVIATION OF POVERTY IN CROSS RIVER STATE - David Adie Alawa; Peter Aniah Betiang; Olabisi Bella; Ekuri, Kelly A; Obibessong Vera M. (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
It is a reality that pepper production has potentials for increasing the income levels of households in Cross River State thereby alleviating their poverty level but the overdependence of external supply of the produce may not be unconnected with the competencies of these households. This study identified the production need gaps of households in pepper production for alleviation of poverty in Cross River State. Four research questions guided the study. The survey research design was adopted for the study. The sample for the study was 438, pepper farmers registered with the Cross River Agricultural Development Programme. A 33-Competency Item Questionnaire (CIQ) for identifying production gaps where households require improvement in pepper production for alleviation of poverty was used for the study and validated by three experts in Departments of Vocational Education and Crop Science, University of Calabar. The reliability of the instrument was determined through Cronbach Alpha method and a coefficient of 0.76 was obtained. Data collected was analyzed using Improvement Needed Index (INI) to answer the research questions. The study found out that households in Cross River State, Nigeria needed improvement in 11 competencies in pre-planting, 6 competencies in planting, 8 competencies in post planting and 8 competencies in marketing operations of pepper production to alleviate their poverty. It was concluded that households generally needed improvement in pepper production to enhance its production and alleviate their poverty. The study recommends that the identified skills be integrated into the extension outreach programme for training of households to ensure greater output of pepper in the study area.